2004
DOI: 10.1590/s0100-83582004000300013
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de doses reduzidas de fluazifop-p-butil no consórcio entre soja e Brachiaria brizantha

Abstract: e SEDIYAMA, C.S. 6 RESUMO -A integração agricultura-pecuária tem se tornado opção vantajosa, beneficiando simultaneamente a produção de grãos e a pecuária. Para viabilizar o consórcio entre culturas e forrageiras, é necessário o manejo adequado da forrageira, evitando-se a interferência negativa desta sobre a cultura. Objetivou-se neste trabalho avaliar os efeitos do fluazifop-pbutil no estabelecimento do consórcio entre soja e braquiária (Brachiaria brizantha). O experimento foi realizado em sistema de pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
22

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 9 publications
0
21
0
22
Order By: Relevance
“…The use of NTS increases the stability of crop production, with minimal environmental disturbance (Franchini et al 2012). However, the long-term sustainability of NTS requires the implementation of crop rotations, minimum soil disturbance, and the cultivation of species with high longevity of straw, such as those of the Urochloa genus (Silva et al 2004).…”
Section: Cultivo Integrado De Cultivares De Soja E Braquiáriamentioning
confidence: 99%
See 1 more Smart Citation
“…The use of NTS increases the stability of crop production, with minimal environmental disturbance (Franchini et al 2012). However, the long-term sustainability of NTS requires the implementation of crop rotations, minimum soil disturbance, and the cultivation of species with high longevity of straw, such as those of the Urochloa genus (Silva et al 2004).…”
Section: Cultivo Integrado De Cultivares De Soja E Braquiáriamentioning
confidence: 99%
“…Therefore, the establishment of fodder grasses before soybean harvest is an alternative that can ensure adequate production of fodder during the period of low water availability. A strategy that can be successfully implemented without causing a significant reduction in the soybean yield is the intercropping between soybean and grass using a high-yield species, such as Urochloa (Silva et al 2004).…”
Section: Cultivo Integrado De Cultivares De Soja E Braquiáriamentioning
confidence: 99%
“…Studies conducted by Crusciol et al (2012Crusciol et al ( , 2014 and Franchini et al (2014) showed changes in this variable between years or among genotypes. The average insertion height of the first pods ranged from 12.5 to 14.5 cm; however, no differences were observed between cultivation modalities, which is in alignment with Franchini et al (2014) and Crusciol et al (2014), but differs from Silva et al (2004) and Crusciol et al (2012). The average height of plants and of the insertion of the first pods are characteristics that vary between soybean genotypes and present some plasticity in relation to environmental changes (Crusciol et al, 2012;Franchini et al, 2014).…”
Section: Resultsmentioning
confidence: 90%
“…The delayed planting of the forage, besides reducing the potential forage competition, allows the application of herbicides for weed control before soybean emergence. If the grass develops more than expected, its growth can also be inhibited by applying herbicides (Cobucci & Portela, 2003;Silva et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation